2000
DOI: 10.1097/00005537-200012000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fiberoptic Nasopharyngoscopy in the Management of the Acute Airway in Angioneurotic Edema

Abstract: FOE is an invaluable tool in the assessment of the compromised airway in patients with angioneurotic edema Laryngeal edema alone is an ominous physical finding. When laryngeal and pharyngeal edema are present together, the physician should consider immediate intervention. Our findings indicate that symptoms, including stridor, hoarseness, and dysphagia, do correlate with disease severity; however, they must be confirmed with fiberoptic visualization. Although sound clinical judgment should always be exercised,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 8 publications
4
36
0
1
Order By: Relevance
“…Although the classification of Chiu et al 12 implied a progression, as none of his patients had isolated glottal or supraglottic involvement without oropharyngeal involvement, other authors have not reported such a progression. 3,14 We classified our patients using the anatomic sites defined by Chiu et al 12 and categorized the edema as involving multiple sites if more than one type was found.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the classification of Chiu et al 12 implied a progression, as none of his patients had isolated glottal or supraglottic involvement without oropharyngeal involvement, other authors have not reported such a progression. 3,14 We classified our patients using the anatomic sites defined by Chiu et al 12 and categorized the edema as involving multiple sites if more than one type was found.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that patients with laryngeal and oropharyngeal angioedema are more likely to be admitted and to require airway intervention. 3,6,[12][13][14] Angioedema is caused by increased vascular permeability with extravasation of fluid into the submucosal or subcutaneous tissues. The exact mechanisms differ among its causes, which include defects in C1 esterase inhibitor (hereditary and acquired angioedema), accumulation of bradykinin (angiotensin-converting enzyme [ACE] inhibitorinduced angioedema), and mast cell degranulation (immunoglobulin E-mediated immediate hypersensitivity).…”
Section: Introductionmentioning
confidence: 99%
“…In approaching the HAE patient with acute oropharyngeal edema, the most important aspect of management rests in early, aggressive support of the airway. The use of fiberoptic nasopharyngoscopy has been shown to be helpful in determining the extent of airway edema in these patients and the need for Emergency Management of Hereditary Angioedema elective intubation (27). The procedure needs to be approached with caution in HAE patients, however, because the associated trauma can accelerate airway closing.…”
Section: Managementmentioning
confidence: 99%
“…66 Up to 20% of patients may present with acute onset of dyspnea, dysphagia, dysphonia and stridor, with rapid progression to life-threatening airway obstruction. 1,7,89,90 Attempts have been made to correlate either the symptoms at presentation or the anatomic site of edema, with subsequent management and outcome. Ishoo et al reviewed 93 episodes of angioedema over a ten-year period, and proposed a staging system by which airway risk could be predicted from the site of presentation.…”
Section: Clinical Presentation Of Acei Angioedemamentioning
confidence: 99%
“…It has been suggested that fibreoptic nasoendoscopy is an invaluable tool in the assessment of the compromised airway in patients with angioedema. Bentsianov et al 90 reported that nine of 14 patients with ACEI-associated angioedema who underwent airway intervention had evidence of laryngeal edema, which is an ominous sign. These authors concluded that when both laryngeal and pharyngeal edema are present, continued observation is critical, as immediate intervention may be warranted, either in the form of endotracheal intubation, or establishment of an emergency surgical airway or tracheostomy.…”
Section: Management Of Angioedemamentioning
confidence: 99%